Advances in Rheumatology - Paiva, Eduardo Santos; Assis, Marcos Renato; Appenzeller, Simone; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Advances in Rheumatology is an international, open access journal publishing pre-clinical, translational and clinical studies on all aspects of paediatric and adult rheumatic diseases, including degenerative, inflammatory and autoimmune conditions. We welcome original research (including systematic reviews and meta-analyses), reviews, guidelines and letters arising from published material. Important notice: Please include the corresponding author$1 (Bs ORCID iD in your manuscript file, as required for SciELO indexing. We recommend all co-authors include an ORCID iD, it is the responsibility of the submitting author to ensure ORCID iDs are included prior to publication. Please take note that as part of the editorial team (EiC, Editor, Editorial Board Member etc.) you would also need to state that in the Conflict of Interest section accordingly, please click here to find out more. .s
Keywords: Rheumatology; Rheumatology